ECONOMIC ASPECTS AND DIRECTIONS OF DEVELOPMENT ENERGY SECTOR IN UKRAINE - BURLAKA, Serhiy; BORETSKA, Tetana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes that the volume of electricity production in the power industry will increase from 185.2 billion kWh in 2005 to 420.1 billion kWh in 2030 (2.3 times). The dominant role of electricity production at thermal (40.8% in 2005, 39.8% in 2030) and nuclear (47.9 and 52.1%, respectively) power plants will be preserved. At the same time, the production of electricity at hydropower plants will increase from 12.1 billion kWh (6.5%) in 2005 to 14.1 billion kWh (3.4%) in 2030 and at the expense of non-traditional and renewable sources energy - from 0.01 billion kWh in 2005 to 2.1 billion kWh in 2030. The costs of electricity in the power grid for its transportation will be reduced from 14.7% in 2005 to at least 8.2% in 2030, and the specific cost of fuel for the production of electricity in the network - from 378.9 to 345.7 in. / kWh The share of electricity generated from imported fuel will decrease from 58.0% in 2005 to 8.2% in 2030 (7 times) (Fig. 4.5). To ensure these volumes of electricity production, the capacity of power plants has been set at UAH 52 million. kW in 2005 to 88.5 million kW in 2030, including thermal power plants from 30.1 to 42.2 million kW and nuclear power plants - from 13.8 to 29.5 million kW. The capacity of the PSP HPP will be increased from UAH 4.7 to UAH 10.5 million. kW, providing the country’s energy system with sufficient shunting capacity. The construction of main power lines, integrated management and emergency protection systems to increase the capacity of power plants, improve electricity supply in some regions, ensure reliable operation of the Unified Energy System and its integration into the European energy system with increasing electricity exports.